2007
DOI: 10.1177/0013916506298798
|View full text |Cite
|
Sign up to set email alerts
|

Territoriality

Abstract: Students' degree of territoriality based on gender and seat preferences in different types of classroom arrangements was studied. The types of classroom arrangements included rows of tablet-arm chairs, U-shaped, clusters, and rows of tables with individual chairs. The study was carried out through a survey at a large public institution in the southeast region of the United States. Results indicate that students who preferred seats at the end of rows of tables with individual chairs and tablet-arm chair arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The factor reduction analysis identified three latent variables accounting for choosing seats: the first is about territoriality (such as quietness, privacy, and furniture) that refers to the personal control of his or her individual space in the library; the second is about visual aspects (such as views, daylighting and orientation); and the third is about social interactions (such as friends, entrance and circulation). Territoriality, in this study, is rated as the most important factor for choosing seats, which is consistent with other research [9]. This study also found that outdoor views came to the second most important factor in students' decision making for seat selection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The factor reduction analysis identified three latent variables accounting for choosing seats: the first is about territoriality (such as quietness, privacy, and furniture) that refers to the personal control of his or her individual space in the library; the second is about visual aspects (such as views, daylighting and orientation); and the third is about social interactions (such as friends, entrance and circulation). Territoriality, in this study, is rated as the most important factor for choosing seats, which is consistent with other research [9]. This study also found that outdoor views came to the second most important factor in students' decision making for seat selection.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies [5][6][7][8] investigated diverse environmental aspects, such as daylighting, sunlight, room acoustics, temperature, which would affect students' perception and preference. Among all potential environmental factors, territoriality is addressed as the most important factor explaining seat preferences in different types of learning environments [9]. In environmental psychology, territoriality refers to how people use space to communicate occupancy of areas or possessions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students sitting in the back rows tend to avoid participation and eye-contact. They are also characterized as showing a stronger need for privacy and territoriality when they repeatedly choose the same seat across different classrooms (Guyot, Byrd, & Caudle, 1980;Kaya & Burgess, 2007;Pedersen, 1994). Benedict and Hoag (2004) found that students who prefer to sit in the front of the classroom have a higher probability of receiving better grades.…”
Section: Study 1: Routine and Well-being In Seating Locationsmentioning
confidence: 99%
“…Research shows that classroom seating arrangement could affect students' behavior. Seating arrangements are important because they have the potential to help to prevent problem behaviors that decrease student attention and diminish available instructional time (Kaya & Burgess, 2007). Kaya and Burges (2007) believed that spatial arrangements in classrooms where students have enough space to move and work on their activities positively affect students' on-task behavior and social interaction.…”
Section: Students Of English Education Department Of Islamic Statementioning
confidence: 99%